Employees' viewpoint on corporate social responsibility (CSR) practices: a preliminary study on Universiti Putra Malaysia - Chan, Tak Jie; Mohd Hasan, Nurul 'Ain; Waheed, Moniza (2015)
In the past few decades, research in Corporate Social Responsibility (CSR) has emerged tremendously in the corporate and academic world. Organisations today realise the significance of being ethical in their business in order to attract external stakeholders and retain employees. However, majority of the previous studies on CSR mainly focuses on the external stakeholders such as customers, media, investors, and government while the influence of CSR practices from an employee’s perspective (as an internal stakeholder) remains largely undiscovered. The current study investigates university as an entity of organisation to explore their CSR practices. The key focus of this study is on one of the research universities in Malaysia, namely Universiti Putra Malaysia (UPM). The purpose of this study is to identify employees’ perception towards selected dimensions of CSR. A quantitative (survey) method and multistage sampling was employed in this study, whereby questionnaires were distributed to 200 UPM staff (academic and non-academic), with only 98 valid respondents. The respondents were selected from Social Science cluster faculties, Science cluster faculties, offices, centers, and divisions. This study focuses primarily on descriptive statistics. The findings show that respondents perceived CSR practices positively and the three (3) specific dimensions, namely compliance with international certified standard, labour rights, and community driven have shown to be the significant aspects of CSR practices perceived by the UPM staff. Further studies to replicate the research in different universities (public or private) in Malaysian to explore more on CSR practices by respective universities were suggested. Future studies were also recommended, in that relationships between CSR, job satisfaction, and corporate reputation need to be carried out in order to see the links between those variables.